The Influence of Individual Characteristics, Work Motivation and Organizational Support on Employee Performance - Muhammad Ilham Sukma; Sukaris Sukaris; Ahmad Qoni Dewantoro; Heru Baskoro (INNOVATION RESEARCH JOURNAL, 2023)
This study aims to determine the effect of individual characteristics, work motivation and organizational support on employee performance (PNS Staff) at the Population and Civil Registry Service, Gresik Regency, East Java Province. This study took a sample of 30 people using a saturated sampling technique while measuring data using a Likert scale. The analysis technique uses test instruments (validity test and reliability test) to test the quality and consistency of measuring instruments, model test/classical assumption test (normality test, multicollinearity test and heteroscedasticity test). The results of the study stated that individual characteristics, work motivation and organizational support had a positive and significant effect on the performance of employees at the Population and Civil Registry Service, Gresik Regency, East Java Province. Based on the results of the t test, the three independent variables have a partial effect. The final conclusion is that the variables of individual characteristics, work motivation, and organizational support are able to explain changes in performance variables.